2016
DOI: 10.22211/cejem/65004
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study on Detonation Wave Propagation in Cylindrical High Explosive Charges with a Wave-shaper

Abstract: Abstract:The use of a cylindrical high-explosive charge with a wave-shaper is an efficient way to obtain an ultra-high pressure and a convergent detonation wave. An analysis of flow fields corresponding to the regular and Mach reflection of detonation waves in a cylindrical high-explosive charge with a wave-shaper is presented in this paper. The pressure, flow velocity and triple point growth angle of the Mach stem were calculated. The Mach stem height was also determined by using the modified Whitham method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It can be seen from the formula that the Mach wave intensity of detonation wave propagating steadily in DLSC is determined by the detonation velocity and the polytropic exponent of the explosive. Using the method of theoretical analysis and numerical simulation, the LE is taken as TNT, the parameters are taken from reference [11] and the HE is Comp B, RDX, Octol and PBX9404 respectively. The results are compared as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen from the formula that the Mach wave intensity of detonation wave propagating steadily in DLSC is determined by the detonation velocity and the polytropic exponent of the explosive. Using the method of theoretical analysis and numerical simulation, the LE is taken as TNT, the parameters are taken from reference [11] and the HE is Comp B, RDX, Octol and PBX9404 respectively. The results are compared as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1970s, through experimental research many scholars have confirmed that the detonation waves in the shaped charge with wave shaper collide with each other can form Mach waves [8]; Tang used high-speed photography to measure the Mach wave formed in the shaped charge, the detonation speed reached 1.9 times of the CÀ J value and the detonation pressure reached 3 times of the CÀ J value [9]; Yang established a theoretical formula for the interaction of detonation waves in shaped charge with the wave shaper according to the Whitham method [10]; Pan pointed out that the critical incident angle of the Mach reflection caused by the detonation wave depends on the polytropic exponent of the explosives and the formula for calculating the pressure and height of the Mach stem was given [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dunne [ 20 , 21 ] obtained the calculation method of the Mach wave parameters, and pointed out that the polytropic exponent of explosives determines the critical incidence angle when detonation waves collide with each other to form Mach waves. Pan [ 22 , 23 ] carried out a more in-depth study on the propagation and collision process of detonation waves in SCWS.…”
Section: Introductionmentioning
confidence: 99%
“…According to the works of Sternberg et al [13][14][15][16], the ratio between the pressure in regions (1) and ( 2) is given by…”
Section: Interaction Analysis Of Detonation Waves Inmentioning
confidence: 99%